If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 1 = -5x + -13 Reorder the terms: 1 + 2x = -5x + -13 Reorder the terms: 1 + 2x = -13 + -5x Solving 1 + 2x = -13 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 1 + 2x + 5x = -13 + -5x + 5x Combine like terms: 2x + 5x = 7x 1 + 7x = -13 + -5x + 5x Combine like terms: -5x + 5x = 0 1 + 7x = -13 + 0 1 + 7x = -13 Add '-1' to each side of the equation. 1 + -1 + 7x = -13 + -1 Combine like terms: 1 + -1 = 0 0 + 7x = -13 + -1 7x = -13 + -1 Combine like terms: -13 + -1 = -14 7x = -14 Divide each side by '7'. x = -2 Simplifying x = -2
| g/2+g+g/4=(2g-1)/12+8 | | 1x(105/(35/7)) | | 7L=41 | | 8L=41 | | 4L=41 | | h-5(h+6)=7(h/3-8) | | X^2+5x+m=0 | | 57.85=1.75+3.6+d | | 57.85=3.6+1.75xd | | 57.85=1.75+3.6xd | | 2L=46 | | 5L=46 | | 6L=46 | | 4l=46 | | 66.55=1.8+1.75*d | | 66.55=1.75+1.8+d | | 13/x=30/42 | | d=66.55-1.75-1.8 | | F(x)=x^3+3x^2 | | 20=6(y-6)+2y | | 50=r+8 | | 50=r+r-8 | | 50-8=r | | 50-8=2r | | X/23=15/33 | | x-11=17-3x | | X/22 | | -7y-21=0 | | c=18+3c | | 5d=40-5d | | 7d-8=-d+56 | | 4j-3=-2j+45 |